Lack of CD4+ T cell percent decrease in alemtuzumab-treated multiple sclerosis patients with persistent relapses - Rolla, Simona; De Mercanti, Stefania Federica; Bardina, Valentina; Horakova, Dana; Habek, Mario; Adamec, Ivan; Cocco, Eleonora; Annovazzi, Pietro; Vladic, Anton; Novelli, Francesco; Durelli, Luca; Clerico, Marinella (Journal of neuroimmunology, 2017)
Alemtuzumab, a highly effective treatment for relapsing remitting multiple sclerosis (RRMS), induces lymphopenia especially of CD4+ T cells. Here, we report the atypical CD4+ T population behaviour of two patients with persistent disease activity despite repeated alemtuzumab treatments. Whereas lymphocytes count decreased and fluctuated accordingly to alemtuzumab administration, their CD4+ cell percentage was not or just mildly affected and was slightly below the lowest normal limit already before alemtuzumab. These cases anticipate further studies aimed to investigate whether the evaluation of the CD4+ cell percentage could represent a helpful tool to address the individual clinical response to alemtuzumab.
Keywords: Multiple Sclerosis; alemtuzumab; Immune reconstitution; Antineoplastic Agents, Immunological; Alemtuzumab; Treatment response; ženské pohlaví; Multiple sclerosis; CD4-pozitivní T-lymfocyty; dospělí; protinádorové látky imunologicky aktivní; Humans; Adult; Female; roztroušená skleróza; CD4-Positive T-Lymphocytes; lidé; CD4+ lymphocytes